Assessment of Risk and Social Impact on Groundwater Pollution by Nitrates. Implementation in the Gallocanta Groundwater Body (NE Spain) - Orellana Macías, José María; Perles-Roselló, María Jesús (IOAP-MDPI, 2022)
Groundwater is an essential resource for humans concerning freshwater supply; therefore, preserving and protecting its quality is necessary. Risk assessment, based on hazard, intrinsic vulnerability information and mapping, may be considered as a key aspect of sustainable groundwater management. An approach has been made by combining the Nitrogen Input Hazard Index and the hydrogeological parameters considered in a modified DRASTIC method. A three-level classification has been used to determine the degree of risk, and the thresholds have been established following measurable criteria related to the potential nitrate concentration in groundwater. The second part of the study focused on estimating the socioeconomic impact of groundwater pollution by relating the degree of risk and social vulnerability to groundwater pollution. The method has been tested in the Gallocanta Groundwater Body (Spain). As a result, a risk map and an impact map are provided. The risk map shows that 67% of the study area can be classified as moderate and high-risk areas, corresponding to high hazard sources located in moderate and high vulnerability zones, whereas the impact of groundwater pollution is classified as moderate in the whole groundwater body. The proposed analysis allows comparison between aquifers in different areas and the results required by water authorities to implement control and mitigation measures.
Keywords: Contaminación; Groundwater contamination; Risk assessment; Pollution sources; IIntrinsic vulnerability; Gallocanta